(untitled) (Web of Teachers: Inderscience Research, 2023)
The article provides a detailed analysis of the current state of the agricultural sector, as well as the level and dynamics of its development in subsequent years. The share of the agricultural sector in GDP and GVA of industries and its changes are also analyzed in detail. The methodology for determining added value in the agricultural sector and on farms is outlined.